Analisis Pendampingan Literasi Budaya Dan Kewarganegaraan Di Era New Normal - Putri Utami, Ima Wahyu; Muzakki, Abdurrohman (WAHANA, 2020)
The purpose of this research is to get a picture of cultural literacy and citizenship that can be done in the new normal era. This type of research used in this research is qualitative research. Data collection techniques used were interviews, observation and documentation. The research instruments used were interview guidelines, observation guidelines and documentation guidelines. The data analysis technique used is the data obtained, then analyzed, presented in accordance with the formulation of the problem, and conclusions drawn. The result of this research is that the implementation of mentoring begins with providing workshops related to cultural literacy and citizenship material, then continued with assistance through the WA group. As for the supporting factors of this mentoring activity, namely the school is very welcame with this mentoring, while the inhibiting factor is, because school activities are carried out online so that they depend heavily on IT-based facilities and infrastructure, but not all teachers master IT. So that in its implementation that requires IT, teachers who have not mastered IT collaborate with teachers who are good at IT.